Rozwiązanie umowy leasingu za porozumieniem stron a przepis art. 709 (15) k.c. Glosa do uchwały Sądu Najwyższego z dnia 26 października 2023 r., III CZP 34/23 - Rzewuska, Magdalena (PRAWO i WIĘŹ, 2025)
The subject of the study is an attempt to analyze the resolution of the Supreme Court of October 26, 2023, III CZP 34/23, in which it was found that if the leasing agreement was terminated by mutual agreement of the parties, the provision of Article 70915 of the Civil Code shall not apply, unless the parties agreed otherwise. This is an important issue not only from a theoretical, but above all from a practical point of view.